Portable Fluorescence Biosensing System for Low-Cost, Quantitative, and Multiplexed Allergen Screening - Hui Chai-Gao; Yevhen Shynkarenko; Silvia Demuru; Nicola Hermann; Patricia-Daiana Boia; Peter Cristofolini; Bradley Petkus; Silvia Generelli; Stefano Cattaneo; Loïc Burr (Proceedings)
A miniaturized multi-array system is being developed for immune-signature testing. The presented system includes microfluidic chips functionalized with allergens for IgE detection and a custom-made portable reader for fast (~1 s), quantitative, and sensitive (500 dye molecules/μm2) detection, with a high spatial resolution (~50–100 μm). The developed solution enables the rapid sensing of allergic reactions at the point of care with a low-cost portable device.